Efektivitas Perkuliahan Pendidikan Agama Islam Dalam Meningkatkan Motivasi Dan Prestasi Dalam Belajar Mahasiswa, Refleksi Pada Mahasiswa Dengan Status Pekerja Di STTI Bontang - Irianto; Panduwinata, Pina; Yusrivan (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
This study aims to describe the effectiveness of Islamic Religious Education learning in increasing student motivation and learning achievement, especially for students with working status at the Bontang Industrial Technology College. Being a working student is certainly not easy to be able to focus on their lecture activities, this makes them also have to focus on the work they have carried out. They are required to work when outside of their class hours and return to work when after their lecture hours, this makes it difficult for students to manage time between college and work. This research is descriptive qualitative research is a research method that seeks to describe and interpret objects in real terms as they are, without manipulating research data. The approach in this research is the educational science approach, in this case the educational science approach is an approach that is systematically organized by having certain methods that are scientific in nature. The results showed that Islamic Religious Education lectures can increase motivation and achievement in student learning, especially for students with working status at STTI Bontang. This is evidenced by very satisfying learning achievements (GPA), high intensity of attendance and involvement and students who show that students have high motivation and lecture strategies applied by doses can run well.